KAJIAN KAPASITAS TAMPUNGAN KOLAM RETENSI DI PERUMAHAN SARIMAS, KELURAHAN SUKAMISKIN, KECAMATAN ARCAMANIK, KOTA BANDUNG - Bima Lutfi Fuad; An An Anisarida (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2021)
The flood was triggered by a decrease in absorption zones as population growth, activity and land requirements for housing or economic activities increased. To overcome the flood, Bandung City created a conservation pond as one of the flood prevention measures designated as one of the most frequent flood forest prevention measures in Sarimas. The purpose of this study is to assess of the capacity of the retention pool in Sarimas housing, Sukamiskin sub-district, Arcamanik subdistrict, Bandung city.Based on a runoff discharge analysis conducted with rain on the 10-year obtained a maximum of water runoff discharge using the method of synthetic hydrograph unit (HSS) Nakayasu of 20.52 m3. The traceability of the flow path carried out still leaves a significant volume of the water tank, with the capacity of the outlet remaining up to 5.01 m3/s capacity for the pump.